Results of surgical treatment of uremic hyperparathyroidism (analysis 67 observations) - E. A. Il'icheva (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
The analysis of the results of surgical treatment of hyperparathyroidism in 63 patients on dialysis replacement renal therapy is presented. A total of 63 primary and 4 secondary (for recurrence) surgical interventions were performed including 12 (17.9 %) - subtotal parathyroidectomy, 8 (11.9 %) - total parathyroidectomy with autotransplantation (type I), 43 (64.2 %) - total parathyroidectomy with removal of the central cellular tissue of the neck, the superior mediastinum and upper horns of the thymus gland with autotransplantation (type II); 3 (4.5 %) - secondary total parathyroidectomy type II and 1 (1.5 %) - secondary parathyroid adenomectomy. With the use of intraoperative monitoring of intact parathyroid hormone, 15 (22.4 %) operations were performed. In the postoperative period from 1 to 134 months, the patients had a decrease in blood levels of calcium, phosphorus and intact parathyroid hormone. Postoperative hypoparathyroidism was detected in 38 cases (56.7 %) of 67 observations: in 5 cases after subtotal parathyroidectomy, 5 - after total parathyroidectomy type I, and 28 - after total parathyroidectomy type II. The permissible level of parathyroid hormone was reached in 13 (19.4 %) cases: 1 - after subtotal parathyroidectomy, 11 - after total parathyroidectomy type II and 1 - after parathyroid adenomectomy. Persistence and relapse of the disease were revealed in 16 observations: 6 - after subtotal parathyroidectomy, 3 - after total parathyroidectomy type I and 7 - after total parathyroidectomy type II. When using intraoperative monitoring of intact parathyroid hormone, there are: 1 observation with the development of the persistence of the disease, 3 - with the permissible level of parathyroid hormone and in 13 cases - with the development of hypoparathyroidism. Based on the results of a comparative analysis of the results of surgical intervention, depending on the type of operation, total type II parathyroidectomy is justified for the prevention of the development of persistence and recurrent HTT (p = 0.01).